Analisis Hukum terhadap Pembiayaan Kesehatan Berbasis Teknologi Fintech serta Implikasinya bagi Sistem Kesehatan Nasional - Desti Emiliani; Marice Simarmata (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study employs a normative juridical approach to examine the legal aspects of implementing financial technology (fintech) in healthcare financing in Indonesia. The rapid development of fintech offers potential solutions for addressing financial barriers in healthcare access. However, it also presents legal and regulatory challenges, particularly concerning consumer protection, data privacy, and institutional coordination. The analysis focuses on several key legal instruments, including Law No. 8 of 1999 on Consumer Protection, Law No. 11 of 2008 on Electronic Information and Transactions (ITE), Law No. 17 of 2023 on Health and its implementing regulation, Government Regulation No. 28 of 2024, and Law No. 27 of 2022 on Personal Data Protection. Additionally, regulations issued by the Financial Services Authority (OJK), which govern the operations of fintech companies in Indonesia, are also considered. The findings indicate that while there is a growing regulatory framework supporting fintech integration into the health sector, several gaps remain, particularly in terms of coordination between regulatory bodies and stakeholders in health and finance. The study identifies the need for comprehensive policy harmonization to ensure that fintech-based healthcare financing systems are secure, transparent, and inclusive. Furthermore, it emphasizes the importance of strengthening data protection mechanisms and enhancing regulatory oversight, especially for fintech services operating in partnership with healthcare providers. As fintech continues to reshape the landscape of healthcare financing, robust legal safeguards must be developed to mitigate potential risks and ensure equitable access to health services. The study concludes by recommending an integrated legal and institutional approach to support the safe and ethical implementation of fintech in Indonesia's healthcare sector.